2021
DOI: 10.1038/s41388-021-02064-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA-methylation patterns imply a common cellular origin of virus- and UV-associated Merkel cell carcinoma

Abstract: Merkel cell carcinoma (MCC) is a neuroendocrine tumor either induced by integration of the Merkel cell polyomavirus into the cell genome or by accumulation of UV-light-associated mutations (VP-MCC and UV-MCC). Whether VP- and UV-MCC have the same or different cellular origins is unclear; with mesenchymal or epidermal origins discussed. DNA-methylation patterns have a proven utility in determining cellular origins of cancers. Therefore, we used this approach to uncover evidence regarding the cell of origin of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Supporting this hypothesis, recent research studying MCPyV+ MCC identified overlapping somatic mutations when performing genetic analysis of a tumor consisting of a benign trichoblastoma derived from the epithelial lineage and MCPyV+ MCC [ 100 ]. Additionally, an analysis of tissue-specific DNA methylation patterns revealed similarities between MCCs and epithelial cancers, including squamous cell carcinoma [ 101 ]. These shared molecular traits further support the hypothesis that MCCs, like Merkel cells, arise from epithelial progenitors in which the MCPyV viral genome had integrated prior to clonal expansion.…”
Section: Role Of Mcpyv In MCCmentioning
confidence: 99%
“…Supporting this hypothesis, recent research studying MCPyV+ MCC identified overlapping somatic mutations when performing genetic analysis of a tumor consisting of a benign trichoblastoma derived from the epithelial lineage and MCPyV+ MCC [ 100 ]. Additionally, an analysis of tissue-specific DNA methylation patterns revealed similarities between MCCs and epithelial cancers, including squamous cell carcinoma [ 101 ]. These shared molecular traits further support the hypothesis that MCCs, like Merkel cells, arise from epithelial progenitors in which the MCPyV viral genome had integrated prior to clonal expansion.…”
Section: Role Of Mcpyv In MCCmentioning
confidence: 99%
“…From a very recent study on DNA-methylation patterns in epithelial and non-epithelial neuroendocrine cancers and MCC-derived cell lines, a common epithelial origin of both MCPyV-positive and -negative MCC cell lines has been suggested. Therefore, the observed differences may be attributed to viral vs. mutation-driven carcinogenesis rather than to the distinct cells of origin [ 45 ].…”
Section: Merkel Cell Carcinomamentioning
confidence: 99%
“…Hence, Merkel cell carcinomas can be subdivided into two major groups: the virus-associated MCCs (VP-MCCs) and the virus-negative MCCs (VN-MCCs or UV-MCCs). Despite evidently different aetiologies, both groups share mutations in vital cell-cycle related genes (meaning they regulate similar molecular paths in different means) [ 29 , 54 , 55 , 56 ], as well as similar disease phenotype [ 57 ] and same emergence location (on sun-exposed regions of the body, such as the head, neck, and limbs [ 58 , 59 ]). On the contrary, VP-MCCs seem to have an insignificant mutational burden and a lower number of somatic mutations compared to VN-MCCs [ 60 , 61 , 62 , 63 ].…”
Section: Merkel Cell Polyomavirus and Merkel Cell Carcinomamentioning
confidence: 99%